Arthroscopic Partial Meniscectomy in Patients With Kellgren-Lawrence Grade 3 Osteoarthritis Shows Clinically Meaningful Improvement in Outcomes - Tyler Warner, B.S; Natalie Lowenstein, M.P.H; Jillian Mazzocca, B.A; Jamie Collins, Ph.D; Elizabeth Matzkin, M.D (Elsevier, 2024)
Purpose: To evaluate patient-reported outcome measures (PROMs) following arthroscopic partial meniscectomy (APM) in patients with Kellgren-Lawrence (KL) grade 3 on preoperative knee radiographs and a symptomatic meniscal tear. Methods: This was a retrospective study design using prospectively collected data from a single institution. Patients were included if they had KL grade 3 osteoarthritis on preoperative radiographs of the knee and completed a trial of nonoperative treatment for at least 6 weeks prior to APM. Patients were excluded if they had inflammatory arthritis, incomplete preoperative and/or 1-year postoperative follow-up data, repeat knee arthroscopy, and concomitant ligamentous injury. Statistical analyses used PROMs, preoperatively and up to 2 years postoperatively, to assess improvement utilizing scales with previously established thresholds, including minimal clinically important difference (MCID) and substantial clinical benefit (SCB). Results: Eighty-two patients met the eligibility criteria (49 women [60%], mean [SD] age, 53.1 [9.3] years). At the 1-year follow-up, most patients achieved MCID: 73% in Knee Injury and Osteoarthritis Outcome Score (KOOS) Pain, 66% in KOOS Symptoms, and 78% in KOOS Activities of Daily Living (ADL). These improvements were similar at the 2-year follow-up: 75%, 72%, and 79% in each subscale, respectively. SCB was also demonstrated 1 year postoperatively, with 56%, 73%, and 71% achieving SCB for the KOOS Pain, Symptoms, and ADL subscales, respectively. These results largely persisted at the 2-year follow-up. Visual analog scale scores for pain also improved at 1- and 2-year postoperative periods with mean improvements from baseline of 2.80 and 2.87 points, respectively. Marx Activity Score decreased on average from baseline to 1- and 2-year follow-up. Conclusions: At a minimum of 1-year follow-up, most patients with KL grade 3 and a meniscal tear achieved MCID and SCB in KOOS Pain, KOOS Symptoms, and KOOS ADL, indicating meaningful outcome improvement for these patients. Level of Evidence: Level IV, therapeutic case series.